Impact of Visionary Leadership on Pro-Social Motivation and Emotional Exhaustion - Zainab Ayaz; Sabahat Javed; Syed Sikandar Wali (UW Journal of Management Sciences, 2021)
Purpose: The study’s goal is to investigate the impact of visionary leadership on prosocial motivation and emotional exhaustion, which will be useful for organizations in the future; it also proves the value of visionary leadership. Making a strategy for staff to reduce emotional exhaustion will be beneficial. It stated that visionary leadership is linked to pro-social motivation in a good way. Design and Methodology: As a sample of 350 respondents from different Pakistani banks from Rawalpindi and Islamabad. The instrument of data collection is questionnaire, which consist of 32 items (questions). There are three parts of questionnaire, one part for each variable. There are 6 items for visionary leadership, 8 items for pro-social motivation, 9 items for emotional exhaustion, and 9 items for demographic data respectively. Findings: Results of regression analysis for first hypothesis revealed that there is a significantly positive relationship between visionary leadership and pro-social motivation. Likewise, the results of regression analysis for second hypothesis revealed that there is a significantly negative relationship between visionary leadership and emotional exhaustion. Implications: The findings of the study implicate that the visionary leadership in an organization promotes the efficiency. The leadership qualities can be enhanced by running leadership development programs.